Sherlock Holmes : Short stories Level 5 - Doyle, Arthur Conan; Hopkins, Andy; Potter, Jocelyn (England Pearson Education Ltd, 2008)
In this book, we join the brilliant detective, Sherlock Holmes, and his friend Dr Watson, in a variety of exciting adventures. These include several suspicious deaths, the mystery of the engineer with the missing thumb, and the strange case of the two men who share a very unusual name.
Keywords: Tham khảo